ETIOLOGI DIAGNOSIS DAN MANAJEMEN SUMBATAN JALAN NAPAS - Suryantarini, Ni Wayan Puspa Wijaya; Ansary, M Fathir Rahadian; Sultan Firdaus, Nadine Aisyah; Artha Jaya Kusuma, I Gusti Ketut (Mandala Of Health, 2024)
Airway obstruction is an emergency condition characterized by occlusion of the lumen of the airway caused by various etiologies, ranging from benign to malignant. Cases of airway obstruction require immediate management starting from an immediate evaluation of the patient’s condition, establishing a diagnosis of etiology and severity, and planning the most appropriate management. Awake intubation, tracheostomy incision, also balloon and stent placement are still quite effective and recommended in various guidelines. Trained medical personnel are essential for the success of the management process of patients with airway obstruction. The high mortality rate makes this condition require attention and treatment as early as possible. The literature review aims to discuss the etiology of airway obstruction that is often encountered in health facilities, as well as the diagnostic modalities and selection of appropriate managements.